Total Ankle Arthroplasty with and without Tibial Stem: Exploring Differences in Post-Operative Migration and Beta Angle - Jetha Tallapaneni MBA; Ali Mirghasemi MD; Zachary Vaupel MD; Paul Fortin MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: The extent of migration of the ankle joint and associated joint space caused by ankle replacement is directly correlated to the efficacy and longevity of the implant. Recent advances have resulted in the increasing use of tibial implants with stems as a means to achieve greater stability. The purpose of this study was to ascertain the differences in said migration between implants with tibial stems and those without in order to conclude which style of replacement leads to greater stability and therefore greater longevity and utility. Methods: A series of cases, which consisted of patients receiving both tibial implants with and without stems, that met the inclusion criteria, was considered for this study in order to determine key differences in outcomes. Twenty patients received tibial implants with stems and twenty patients received tibial implants without stems. The average patient ages between the two groups were not significantly different- the mean age of patients with the stem was 65.4 compared to 68.7 for the non-stem group. The key variables considered included migration (AP and anterior/posterior, DTA, TTA, beta angles, gamma angles, coronal translation, and talar tilt. Two tailed T-tests were utilized to determine statistically significant results. Results: Differences in measurements from the first post-operative weight bearing x-ray to the most recent weight bearing x-ray were considered. The mean time between these two x-rays was 24 months for the patients who received tibial implants with stems and XX months for patients who received tibial implants without stems. Across the population considered, it was found that patients recieving the implants without the stem had significantly less migration in the AP view X-rays when compared to their tibial implant with stem patient counterparts in both X-rays considered (p< 0.03). Additionally, patients without the tibial stem had significantly larger beta angles than patients with the tibial stem in both x-rays considered (p< 0.04). Conclusion: Ankle replacements utilizing tibial stems lead to greater rates of migration when compared to those without said stems. Therefore, the supposed benefit of the stem falls into question. Greater beta angles are seen with tibial implants without stems, however. Further research regarding the efficacy and long-term outcomes of each of these implants for total ankle replacement must be conducted to refine these findings further.